Resuscitating the Baby after Shoulder Dystocia - Savas Menticoglou; Carol Schneider (Case Reports in Obstetrics and Gynecology)
Background. To propose hypovolemic shock as a possible explanation for the failure to resuscitate some babies after shoulder dystocia and to suggest a change in clinical practice. Case Presentation. Two cases are presented in which severe shoulder dystocia was resolved within five minutes. Both babies were born without a heartbeat. Despite standard resuscitation by expert neonatologists, no heartbeat was obtained until volume resuscitation was started, at 25 minutes in the first case and 11 minutes in the second. After volume resuscitation circulation was restored, there was profound brain damage and the babies died. Conclusion. Unsuspected hypovolemic shock may explain some cases of failed resuscitation after shoulder dystocia. This may require a change in clinical practice. Rather than immediately clamping the cord after the baby is delivered, it is proposed that (1) the obstetrician delay cord clamping to allow autotransfusion of the baby from the placenta and (2) the neonatal resuscitators give volume much sooner.